2016
DOI: 10.1039/c6md00043f
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid transport proteins: targeting FATP2 as a gatekeeper involved in the transport of exogenous fatty acids

Abstract: Summary The fatty acid transport proteins (FATP) are classified as members of the Solute Carrier 27 (Slc27) family of proteins based on their ability to function in the transport of exogenous fatty acids. These proteins, when localized to the plasma membrane or at intracellular membrane junctions with the endoplasmic reticulum, function as a gate in the regulated transport of fatty acids and thus represent a therapeutic target to delimit the acquisition of fatty acids that contribute to disease as in the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 130 publications
1
41
0
Order By: Relevance
“…Although the functions of these genes remain unknown in fish, genetic studies targeting FATP2, FATP4 and CD36 in mice have confirmed their function as fatty acid transporters in the liver and intestine (Anderson & Stahl, ; Pepino, Kuda, Samovski, & Abumrad, ). Evidences indicate that FATP2, FATP4 and CD36 play a role in intestinal lipid absorption in mammals (Anderson & Stahl, ; Black, Ahowesso, Montefusco, Saini, & Dirusso, ; Pepino et al, ). Furthermore, knockdown of mouse FATP2 is able to reverse established, high‐fat diet‐induced hepatosteatosis, and FATP2 plays a prominent role in hepatic fatty acid uptake (Falcon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the functions of these genes remain unknown in fish, genetic studies targeting FATP2, FATP4 and CD36 in mice have confirmed their function as fatty acid transporters in the liver and intestine (Anderson & Stahl, ; Pepino, Kuda, Samovski, & Abumrad, ). Evidences indicate that FATP2, FATP4 and CD36 play a role in intestinal lipid absorption in mammals (Anderson & Stahl, ; Black, Ahowesso, Montefusco, Saini, & Dirusso, ; Pepino et al, ). Furthermore, knockdown of mouse FATP2 is able to reverse established, high‐fat diet‐induced hepatosteatosis, and FATP2 plays a prominent role in hepatic fatty acid uptake (Falcon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies tried to show the relevance of transporters in different models. The intestinal LCFA uptake of fatty acid transport protein 2 (FATP2)-knockout mice has not been observed, but selective FATP2 inhibitors, such as Lipofermata, show 80% attenuation of LCFA uptake across the gut [ 12 , 13 ]. A 48% decrease of FATP4 protein level leads to a 40% reduction of LCFA uptake in isolated primary enterocytes of mice, whereas no change of lipid uptake has been detected in vivo.…”
Section: The Role Of Intestinal Fatty Acid Glucose and Fructose Umentioning
confidence: 99%
“…The LCFA transporter with the highest incidence in the intestinal system is still debated. The most represented opinion supported FATP4 [ 62 , 64 , 65 , 70 ], but since there was no effect of potential inhibitors in vivo, Black et al proposed FATP2 as a major intestinal LCFA transporter recently [ 13 ]. However, the ineffective in vivo studies of FATP4 inhibitors could relate to the inactivation of the inhibitors by the gut microbiome and/or to the large capacity of the small intestine regarding fat absorption [ 71 ].…”
Section: Transport Mechanisms and Binding Sites Of Intestinal Satumentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variations in the porcine SLC26A6 gene are related to divergent lipid metabolism processes 35 . Although little is known about the role of SLC26A6 in the context of obesity, members of the fatty acid transport proteins are widely discussed as regulators of energy homeostasis, exogenous fatty acid uptake, and thermogenesis 36 .…”
Section: Discussionmentioning
confidence: 99%